Konsep Ḥijāb dalam Al-Qur’an (Implementasi Semantik Toshihiko Izutsu Terhadap Kosakata Ḥijāb dalam Al-Qur’an) - Farid Muhlasol (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2023)
The discussion about the term ḥijāb has recently become interesting because the debate about its meaning is ambiguous in the linguistic aspect. The search for the true meaning is necessary so that the meaning of the word ḥijāb does not deviate from its original meaning. For this reason, it is necessary to have a way to explore the meaning of the word ḥijāb through a semantic approach. This study used the library research method, which was the data collected from the library. The approach used in this research was Toshihiko Izutsu's Semantics, which is known as a technique to reveal the philosophy of life or world view of the Qur'an (weltanschauung) by analyzing key vocabulary in the Qur'an. This study draws the conclusion that the word ḥijāb and its derivations are mentioned in the Qur'an eight times as contained in QS al-A'rāf [7]: 46, QS Maryam [19]: 17, QS al-Isrā’ [17]: 45, QS al-Aḥzāb [33]: 53, QS Ṣād [38]: 32, QS Fusṣilat [41]: 5, QS asy-Syūrā [42 ]: 51, and QS Al-Muṭaffifīn [83]: 15. This study found two weltanschauung or views of life regarding ḥijāb, namely: 1) The view of ḥijāb ḥissi (can be seen by the five senses) is to do things that are forbidden by Allah SWT for women who are not mahrams and ḥub ad-dunya or love the world, and 2) The view of ḥijāb ma'nawī (cannot be seen by the five senses) is a disbeliever whose heart is closed from the guidance of faith and a servant's conversation with his Lord.